Graphite negative electrode plate, preparation method thereof and lithium ion battery

By performing three magnetization treatments on the graphite negative electrode sheet, the high magnification and excellent cycling performance of the lithium-ion battery are achieved, the problem of difficulty in embedded and disengagement of lithium-ion is solved, and the overall electrochemical performance of the battery is improved.

CN119133370AActive Publication Date: 2024-12-13SHANGHAI XUANYI NEW ENERGY DEV CO LTD

Patent Information

Application Number
CN202411363259.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-13
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The negative electrode sheet of existing lithium-ion batteries has difficulty in embedded and disengaging lithium ions during charging and discharging, resulting in poor rate performance.

Method used

By performing three magnetization treatments on the graphite negative electrode sheet, the graphite active material is arranged in a directional arrangement using the magnetic field, shortening the migration path of lithium ions during the deintercalation process, thereby improving the charge and discharge rate and cycling performance.

Benefits of technology

The charge and discharge rate performance and long cycle life of the graphite negative electrode sheet are significantly improved, so that the lithium-ion battery can exhibit high capacity, first-time efficiency and long cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133370A_ABST
    Figure CN119133370A_ABST
Patent Text Reader

Abstract

The invention provides a graphite negative electrode plate, a preparation method thereof and a lithium ion battery. The preparation method comprises the following steps: S1, mixing materials; step S2, coating is carried out; the coated electrode plate is subjected to N sets of magnetization treatment periodically, a graphite negative electrode plate is obtained, and N is an integer larger than or equal to 1; each group of magnetization treatment comprises first magnetization carried out along a first direction, second magnetization carried out along a second direction and third magnetization carried out along a third direction, the first magnetization, the second magnetization and the third magnetization are carried out in any sequence, the first direction is perpendicular to the plane direction of the coated electrode slice, the second direction is perpendicular to the third direction, and the third direction is perpendicular to the plane direction of the coated electrode slice. And the direction is parallel to the plane direction of the coated electrode plate. According to the invention, the coated pole piece coated with the graphite active material slurry is magnetized for three times to obtain the oriented graphite negative pole piece, so that the migration path of lithium ions in the de-intercalation process is shortened, and high charge-discharge rate and excellent cycle performance are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a graphite negative electrode sheet, a preparation method thereof and a lithium ion battery. Background Art

[0002] With the rapid development of electric vehicles, people are eager for electric vehicles to have long driving range and fast charging and discharging performance. Therefore, the demand for high-capacity and high-rate lithium-ion batteries is increasing year by year. Lithium titanate has a high charge and discharge rate due to its unique crystal structure. However, its low gram capacity and high voltage platform seriously restrict its application in electric vehicles. Graphite has a gram capacity more than twice that of lithium titanate and has become the main negative electrode material for electric vehicles. However, as the demand for power of electric vehicle batteries continues to increase, higher requirements are placed on the charge and discharge rate performance of negative electrode materials.

[0003] At present, in order to overcome the defect of low charge and discharge rate of graphite, most methods are to modify the graphite material. For example, Chinese patent CN201410787061.7 uses asphalt to coat graphite and high-temperature graphitization to prepare a fast-charging graphite lithium-ion battery negative electrode material. In this method, the asphalt coated on the surface of graphite is converted into graphite carbon through high-temperature graphitization, and its performance is close to that of bulk graphite, so the rate performance improvement is limited. Chinese patent CN201710186013.6 uses high-temperature graphitization to prepare artificial graphite, and then mixes it with asphalt for carbonization to prepare a fast-charging graphite lithium-ion battery negative electrode material. Although this method is to coat amorphous carbon on the surface of graphite, it requires multiple high-temperature heat treatments, the process is complex, the energy consumption is high, and the carbon coated on the surface has not been subjected to high-temperature graphitization treatment. The amorphous carbon has many structural defects, the material has low initial efficiency, and the cycle performance is poor.

[0004] Based on this, how to provide a graphite negative electrode sheet and its corresponding preparation method to more significantly improve the electrochemical performance of the negative electrode sheet and ultimately make the lithium-ion battery in which it is located show higher capacity, first efficiency and cycle stability is one of the important technical problems that need to be solved in this field. Summary of the invention

[0005] The main purpose of the present invention is to provide a graphite negative electrode sheet, a preparation method thereof and a lithium ion battery, so as to solve the problem of poor rate performance of the battery caused by the difficulty of lithium ion insertion and extraction in the negative electrode sheet of the lithium ion battery during the charge and discharge process in the prior art.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a graphite negative electrode sheet, comprising the following steps: step S1, mixing: adding graphite, a conductive agent and a binder to a solvent, and mixing to obtain a slurry; step S2, coating: preparing a current collector, and coating the slurry on at least one side surface of the current collector to obtain a coated electrode sheet, wherein the coated electrode sheet has a length direction and a width direction that are perpendicular to each other; step S3, magnetization: periodically performing N groups of magnetization treatments on the coated electrode sheet to obtain a graphite negative electrode sheet, wherein N is an integer ≥1; each group of magnetization treatments includes a first magnetization performed along a first direction, a second magnetization performed along a second direction, and a third magnetization performed along a third direction, and the first magnetization, the second magnetization and the third magnetization are performed in any order, and the first direction is perpendicular to the plane direction of the coated electrode sheet, and the second direction and the third direction are perpendicular to each other and parallel to the plane direction of the coated electrode sheet.

[0007] Furthermore, in step S3, N=1, the first direction is perpendicular to the plane direction of the coated electrode sheet; the second direction is parallel to the plane direction of the coated electrode sheet and perpendicular to the length direction of the coated electrode sheet; the third direction is parallel to the plane direction of the coated electrode sheet and perpendicular to the width direction of the coated electrode sheet; preferably, the magnetic field strength used for the three magnetization treatments is independently 0.5~1.5T.

[0008] Furthermore, the time of the first magnetization, the second magnetization and the third magnetization are each independently 1 to 120 seconds.

[0009] Furthermore, the particle size D50 of the graphite is 3 to 20 μm; preferably, the graphite is natural graphite and / or artificial graphite, more preferably natural graphite.

[0010] Furthermore, the ratio of the sum of the weight of the conductive agent and the binder to the weight of the graphite is (10-2): (90-98), the solid content of the slurry is 30-60%, and the coating viscosity is 3000-7000 Pa·s.

[0011] Furthermore, the conductive agent is selected from one or more of acetylene black, carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene; and / or the binder is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyaniline and citric acid; preferably, the solvent is water.

[0012] Furthermore, step S1 also includes: adding the first binder to the solvent, performing a first mixing to obtain an intermediate slurry; adding graphite, a conductive agent and a second binder to the intermediate slurry, performing a second mixing to obtain a slurry; preferably, the first mixing time is 1 to 2 hours, and the second mixing time is 3 to 9 hours; preferably, the first binder and the second binder are each independently one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyaniline and citric acid; more preferably, mixing is achieved using a twin-screw mixer and / or a double planetary mixer.

[0013] Another aspect of the present invention provides a graphite negative electrode sheet prepared by the above-mentioned method for preparing a graphite negative electrode sheet.

[0014] Furthermore, the OI value of the graphite negative electrode sheet is 0.1-1.

[0015] Another aspect of the present invention provides a lithium-ion battery, comprising a negative electrode sheet, a positive electrode sheet and an electrolyte, wherein the positive electrode sheet is the above-mentioned graphite negative electrode sheet.

[0016] By applying the technical solution of the present invention, an oriented graphite negative electrode sheet is obtained by subjecting a coated electrode sheet coated with a graphite active material slurry to three magnetization treatments, which shortens the migration path of lithium ions during the deintercalation process, thereby ensuring a high charge and discharge rate and excellent cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 This is a SEM photograph of the graphite negative electrode sheet obtained in Example 1 at a magnification of 5k;

[0019] Figure 2 This is a SEM photograph of the graphite negative electrode sheet obtained in Example 1 at a magnification of 2k;

[0020] Figure 3 This is a SEM photograph of the graphite negative electrode sheet obtained in Comparative Example 1 at a magnification of 5k;

[0021] Figure 4 This is a SEM photograph of the graphite negative electrode sheet obtained in Comparative Example 1 at a magnification of 2k;

[0022] Figure 5 XRD comparison spectra of the graphite negative electrode sheets obtained in Example 1 and Comparative Example 1 respectively (the upper one is Example 1, and the lower one is Comparative Example 1). DETAILED DESCRIPTION

[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0024] As described in the background technology, the prior art has a problem of poor rate performance of the battery due to the difficulty of lithium ion insertion and extraction in the negative electrode sheet of the lithium ion battery during the charging and discharging process. In order to solve the above technical problems, the present invention provides a method for preparing a graphite negative electrode sheet, comprising the following steps: step S1, mixing: adding graphite, a conductive agent and a binder to a solvent, mixing to obtain a slurry; step S2, coating: preparing a current collector, and coating the slurry on at least one side of the current collector to obtain a coated electrode sheet, the coated electrode sheet having a length direction and a width direction perpendicular to each other; step S3, magnetization: periodically performing N groups of magnetization treatments on the coated electrode sheet to obtain a graphite negative electrode sheet, wherein N is an integer ≥1; each group of magnetization treatments includes a first magnetization performed along a first direction, a second magnetization performed along a second direction, and a third magnetization performed along a third direction, the first magnetization, the second magnetization and the third magnetization are performed in any order, and the first direction is perpendicular to the plane direction of the coated electrode sheet, the second direction and the third direction are perpendicular to each other, and parallel to the plane direction of the coated electrode sheet.

[0025] The present invention obtains a specially oriented graphite negative electrode sheet by subjecting a coated electrode sheet coated with graphite active material slurry to multiple magnetization treatments of times multiple of 3, which shortens the migration path of lithium ions during the deintercalation process, thereby ensuring a high charge and discharge rate and excellent cycle performance of the material. Specifically, during the preparation of the electrode sheet, the electrode sheet coated with the active slurry is placed in a magnetic field in a specific direction. Due to the diamagnetic nature of graphite, it will present a directional arrangement under the action of the magnetic field, thereby significantly reducing the OI value of graphite and the tortuosity of the graphite negative electrode sheet, and improving the charge and discharge rate performance and long cycle life of the graphite negative electrode sheet.

[0026] However, it should be noted that the preparation method provided by the present invention is targeted at graphite as a raw material. Compared with the one-dimensional negative electrode activated carbon materials commonly used in the art, such as conductive carbon black, it can use its own anti-magnetism to achieve the effect of particle rearrangement. Compared with other two-dimensional negative electrode activated carbon materials commonly used in the art, especially graphene, it has the characteristics of being easy to disperse and the material itself has a certain self-supporting ability and can act as the main negative electrode active material in lithium-ion batteries, so that under the action of a specific magnetic field, the final orientation effect can be achieved. In the preparation process, unlike the related experimental ideas commonly used in the art of pre-treating the graphite material itself to improve the intrinsic properties of the graphite material, the present invention creatively limits the processing objects of multiple magnetization treatments to coated electrode sheets coated with graphite active materials. With this arrangement, a graphite negative electrode sheet with highly oriented graphite active materials on it and excellent rate performance and long cycle performance is finally obtained.

[0027] In several typical embodiments, in order to enable the cross section of the graphite active material to be more effectively oriented vertically on the surface of the negative electrode sheet, it is preferred that N=1 in step S3, the first direction is perpendicular to the plane direction of the coated electrode sheet; the second direction is parallel to the plane direction of the coated electrode sheet and perpendicular to the length direction of the coated electrode sheet; the third direction is parallel to the plane direction of the coated electrode sheet and perpendicular to the width direction of the coated electrode sheet. Furthermore, the magnetic field intensity used for the three magnetization treatments is independently 0.5~1.5T. After a large number of experiments, the inventors designed the magnetic field directions used for the three magnetization treatments, and at the same time optimized the above-mentioned specific intensity range, and obtained a graphite negative electrode sheet with higher rate performance and better long cycle stability under this condition. In order to enhance the magnetization effect, improve the orientation degree of the graphite material, and ultimately improve the rate performance of the electrode sheet, it is more preferred that the time of the first magnetization, the second magnetization and the third magnetization is independently 1~120s.

[0028] Furthermore, in order to make the tertiary magnetization orientation more effective, thereby significantly improving the rate performance of the obtained graphite negative electrode sheet, the particle size D50 of the graphite is preferably 3 to 20 μm. In several typical embodiments, the graphite is natural graphite and / or artificial graphite. In several more preferred embodiments, the graphite is natural graphite, because natural graphite is generally in the form of large flakes, and the antimagnetic characteristics are more obvious.

[0029] In the process of preparing the slurry, in order to improve its dispersion uniformity and ductility on the surface of the electrode sheet, so that the graphite active material is better dispersed on the surface of the electrode sheet, and the rate performance of the obtained electrode sheet is better, in several typical embodiments, the ratio of the sum of the weight of the conductive agent and the binder to the weight of the graphite is preferably (10-2): (90-98), the solid content of the slurry is 30-60%, and the coating viscosity is 3000-7000 Pa·s.

[0030] In several typical embodiments, the conductive agent is selected from one or more of acetylene black, carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene; and / or, the binder is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyaniline and citric acid. In theory, both the conductive agent and the binder can be selected from the types commonly used in the art, but the inventor has selected the above specific types through a large number of experiments, and found that they can better adapt to the graphite negative electrode active system provided by the present invention, and can more effectively promote the orientation of the graphite material on the surface of the electrode sheet, thereby more significantly improving the rate performance of the resulting graphite negative electrode sheet. And in order to improve the uniformity and stability of the slurry system, optimize its uniform distribution on the surface of the electrode sheet, and improve the cycle stability, the preferred solvent is water.

[0031] Furthermore, in order to improve the uniformity of dispersion of each component and the stability of the slurry system during the preparation of the slurry, and ultimately strengthen the orientation of the graphite material and improve the rate performance of the pole piece, the preferred step S1 also includes: adding the first binder to the solvent, performing a first mixing to obtain an intermediate slurry; adding graphite, a conductive agent and a second binder to the intermediate slurry, performing a second mixing to obtain a slurry. Furthermore, after a large number of experiments, the inventors preferably selected the first mixing time as 1 to 2 hours and the second mixing time as 3 to 9 hours, and obtained a slurry with better dispersion and uniformity under these conditions, so as to more effectively optimize the structure of the surface coating layer of the obtained graphite negative electrode sheet and improve the various properties of the pole piece. In several typical embodiments, the first binder and the second binder are each independently one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyaniline and citric acid. In several more preferred embodiments, mixing is achieved using a twin-screw mixer and / or a double planetary mixer. Compared with other mixing methods, the slurry mixed by these two types of equipment has a higher dispersion uniformity and a higher mixing efficiency.

[0032] Another aspect of the present invention provides a graphite negative electrode sheet prepared by the above-mentioned method for preparing a graphite negative electrode sheet. The obtained graphite negative electrode sheet has a highly oriented graphite negative electrode active material thereon, which effectively shortens the migration path of lithium ions during the insertion and extraction process, thereby having a high charge and discharge rate and cycle performance.

[0033] In particular, further, the OI value of the graphite negative electrode sheet is 0.1-1, that is, the graphite negative electrode active material is highly oriented on the electrode sheet. In the application process of the negative electrode sheet, Li + It can perform more efficient deintercalation along the end face of the graphite negative electrode, significantly reducing the tortuosity of the graphite negative electrode, thereby more effectively improving the electrical properties of the resulting negative electrode sheet, especially the long cycle performance.

[0034] Another aspect of the present invention provides a lithium-ion battery, comprising a negative electrode sheet, a positive electrode sheet and an electrolyte, wherein the positive electrode sheet is the above-mentioned graphite negative electrode sheet.

[0035] Because the end face of the graphite negative electrode active material on the surface of the above-mentioned graphite negative electrode sheet is perpendicular to the negative electrode current collector, it is highly oriented and has a high charge and discharge rate and excellent cycle performance. Therefore, when it is used as a negative electrode element in a lithium-ion battery, the resulting lithium-ion battery also exhibits high capacity, high initial efficiency, high charge and discharge rate and long cycle performance.

[0036] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0038] Example 1

[0039] Preparation of a graphite negative electrode sheet:

[0040] 0.2 kg of binder CMC and 10 kg of distilled water were added to a double planetary mixer and mixed for 2 hours. Then 0.1 kg of conductive carbon black, 9.5 kg of natural graphite (d50 is 12.0 μm) and 0.2 kg of binder PAA were added in sequence and mixed for 3 hours. After sieving to remove bubbles, the slurry was transferred to a coater for coating. At this time, the viscosity of the slurry was 4100 mPa·s. After coating, a coated electrode was obtained.

[0041] Before drying the coated pole piece, it is first placed in a 0.6T magnetic field for a first magnetization treatment for 5s, then placed in a 0.8T magnetic field for a second magnetization treatment for 5s, and finally placed in a 1.0T magnetic field for a third magnetization treatment for 10s. The magnetic field direction of the first magnetization treatment is perpendicular to the coated surface of the coated pole piece, the magnetic field direction of the second magnetization treatment is parallel to the coated surface on the coated pole piece and perpendicular to the short side, and the magnetic field direction of the third magnetization treatment is parallel to the coated surface on the coated pole piece and perpendicular to the long side.

[0042] After three magnetization treatments, the normal pole piece drying and winding and subsequent pole piece processing are carried out to obtain a graphite negative electrode sheet, and its SEM photo with a magnification of 5k is shown in Figure 1 , see SEM photos with a magnification of 2k Figure 2 , XRD spectrum see Figure 5 .

[0043] Example 2

[0044] Preparation of a graphite negative electrode sheet:

[0045] 0.2 kg of binder CMC and 10 kg of distilled water were added to a double planetary mixer and mixed for 2 hours. Then 0.1 kg of conductive carbon black, 9.5 kg of natural graphite (d50 is 12.0 μm) and 0.2 kg of binder PAA were added in sequence and mixed for 3 hours. After sieving to remove bubbles, the slurry was transferred to a coater for coating. At this time, the viscosity of the slurry was 4100 mPa·s. After coating, a coated electrode was obtained.

[0046] Before drying the coated pole piece, it is first placed in a 0.6T magnetic field for a first magnetization treatment for 10 seconds, then placed in a 0.8T magnetic field for a second magnetization treatment for 5 seconds, and finally placed in a 1.0T magnetic field for a third magnetization treatment for 10 seconds. The magnetic field direction of the first magnetization treatment is perpendicular to the coated surface of the coated pole piece, the magnetic field direction of the second magnetization treatment is parallel to the coated surface on the coated pole piece and perpendicular to the short side, and the magnetic field direction of the third magnetization treatment is parallel to the coated surface on the coated pole piece and perpendicular to the long side.

[0047] After three magnetization treatments, normal pole piece drying and winding and subsequent pole piece processing are carried out to obtain a graphite negative electrode sheet.

[0048] Example 3

[0049] Preparation of a graphite negative electrode sheet:

[0050] 0.2 kg of binder CMC and 10 kg of distilled water were added to a double planetary mixer and mixed for 2 hours. Then, 0.1 kg of conductive carbon black, 9.5 kg of natural graphite (d50 is 12.0 μm) and 0.2 kg of binder PAA were added in sequence and mixed for 3 hours. After sieving and removing bubbles, the slurry was transferred to a coater for coating. At this time, the viscosity of the slurry was 4100 m Pa·s. After coating, a coated electrode was obtained.

[0051] Before drying the coated pole piece, it is first placed in a 0.6T magnetic field for a first magnetization treatment for 10 seconds, then placed in a 0.8T magnetic field for a second magnetization treatment for 10 seconds, and finally placed in a 1.0T magnetic field for a third magnetization treatment for 10 seconds. The magnetic field direction of the first magnetization treatment is perpendicular to the coated surface of the coated pole piece, the magnetic field direction of the second magnetization treatment is parallel to the coated surface on the coated pole piece and perpendicular to the short side, and the magnetic field direction of the third magnetization treatment is parallel to the coated surface on the coated pole piece and perpendicular to the long side.

[0052] After three magnetization treatments, normal pole piece drying and winding and subsequent pole piece processing are carried out to obtain a graphite negative electrode sheet.

[0053] Example 4

[0054] Preparation of a graphite negative electrode sheet:

[0055] The only difference between this embodiment and embodiment 1 is that the graphite used is artificial graphite instead of natural graphite.

[0056] Example 5

[0057] Preparation of a graphite negative electrode sheet:

[0058] The difference between this embodiment and embodiment 1 is that the magnetic field strengths used for the three magnetizations are different. Specifically, the magnetic field strength of the first magnetization treatment is changed to 0.3T, the magnetic field strength of the second magnetization treatment is changed to 0.3T, and the magnetic field strength of the third magnetization treatment is changed to 2.0T.

[0059] Example 6

[0060] Preparation of a graphite negative electrode sheet:

[0061] The difference between this embodiment and embodiment 1 is that the magnetic field strengths used for the three magnetizations are different. Specifically, the magnetic field strength of the first magnetization treatment is changed to 2.0T, the magnetic field strength of the second magnetization treatment is changed to 2.0T, and the magnetic field strength of the third magnetization treatment is changed to 0.3T.

[0062] Example 7

[0063] Preparation of a graphite negative electrode sheet:

[0064] The only difference between this embodiment and embodiment 1 is that the d50 of the natural graphite used is 6.0 μm.

[0065] Example 8

[0066] Preparation of a graphite negative electrode sheet:

[0067] The only difference between this embodiment and embodiment 1 is that the d50 of the natural graphite used is 18.0 μm.

[0068] Example 9

[0069] Preparation of a graphite negative electrode sheet:

[0070] The difference between this embodiment and embodiment 1 is that the components in the slurry formula are different, specifically: 0.2 kg of binder CMC, 0.2 kg of binder SBR, 0.1 kg of conductive agent carbon black, 9.5 kg of natural graphite, and 10 kg of distilled water. The solid content of the obtained slurry is 50% and the viscosity is 3600 mPa·s.

[0071] Example 10

[0072] Preparation of a graphite negative electrode sheet:

[0073] The difference between this embodiment and embodiment 1 is that the amount of each component in the slurry formula is different, specifically: the binder CMC is 0.1 kg, the binder PAA is 0.3 kg, the conductive agent carbon black is 0.1 kg, the natural graphite is 9.5 kg, and the distilled water is 10 kg. The solid content of the obtained slurry is 50% and the viscosity is 3600 mPa·s.

[0074] Embodiment 11

[0075] Preparation of a graphite negative electrode sheet:

[0076] The only difference between this embodiment and embodiment 1 is that in the process of preparing the slurry, the first mixing (i.e., mixing of CMC and deionized water) takes 30 minutes, and the second mixing (i.e., mixing to obtain the final slurry) takes 10 hours.

[0077] Example 12

[0078] Preparation of a graphite negative electrode sheet:

[0079] The only difference between this embodiment and embodiment 1 is that in the preparation process of the slurry, the first mixing (i.e., mixing of CMC and deionized water) takes 5 hours, and the second mixing (i.e., mixing to obtain the final slurry) takes 2 hours.

[0080] Comparative Example 1

[0081] Preparation of a graphite negative electrode sheet:

[0082] The difference between this comparative example and Example 1 is that the coated pole piece is not subjected to three magnetization treatments, but is directly dried to obtain a negative electrode sheet, and a SEM photograph thereof with a magnification of 5k is shown in FIG. Figure 3 , see SEM photos with a magnification of 2k Figure 4 , XRD spectrum see Figure 5 .

[0083] Comparative Example 2

[0084] Preparation of a graphite negative electrode sheet:

[0085] The only difference between this comparative example and Example 4 is that the coated pole piece is not subjected to three magnetization treatments, but is directly dried to obtain the negative electrode piece.

[0086] Comparative Example 3

[0087] Preparation of a graphite negative electrode sheet:

[0088] The only difference between this comparative example and Example 1 is that before mixing, the natural graphite used is subjected to three magnetization treatments with the same magnetic field strength as in Example 1, and then the natural graphite after the magnetization treatment is mixed with other components to prepare a slurry, and a graphite negative electrode sheet is obtained after coating and drying, and no magnetization treatment is performed after obtaining the coated electrode sheet.

[0089] Comparative Example 4

[0090] Preparation of a graphite negative electrode sheet:

[0091] The only difference between this comparative example and Example 1 is that the natural graphite is replaced by an equal weight of graphene, the model of which is GMC96 produced by Adeka Company of Japan.

[0092] Comparative Example 5

[0093] Preparation of a graphite negative electrode sheet:

[0094] The difference between this comparative example and Example 1 is that the coated pole piece is subjected to magnetization treatment only twice, i.e., the first magnetization treatment with a magnetic field intensity of 0.6 T and a time of 5 s, and the second magnetization treatment with a magnetic field intensity of 0.8 T and a time of 10 s. The magnetic field direction of the first magnetization treatment is perpendicular to the coated surface of the coated pole piece, and the magnetic field direction of the second magnetization treatment is parallel to the coated surface on the coated pole piece and perpendicular to the short side.

[0095] Comparative Example 6

[0096] Preparation of a graphite negative electrode sheet:

[0097] The only difference between this comparative example and Example 1 is that the coated pole piece is magnetized only once, that is, the magnetization treatment is performed with a magnetic field intensity of 0.6 T and a time of 5 s, and the direction of the magnetic field is perpendicular to the coated surface of the coated pole piece.

[0098] Test Method

[0099] Pole piece OI value test: carried out using XRD analysis method.

[0100] Battery assembly: LiNi 0.8 Co 0.1 Mn 0.1 The O2 electrode was used as the positive electrode, the N / P ratio was designed to be 1.1, 1 mol / L LiPF6 EC / EMC (volume ratio of 3:7) solution was used as the electrolyte, and the celgard2400 microporous diaphragm was used as the diaphragm. The graphite negative electrode sheets obtained in each embodiment and comparative example were assembled to obtain a battery cell, thereby obtaining a 10Ah battery sample.

[0101] Battery performance test: Under room temperature conditions, the obtained battery samples were charged and discharged at constant current and constant voltage at a current density of 0.1C for 1 week, then charged and discharged at a current density of 1C for the second week, and finally charged and discharged at a current density of 0.5C for 100 weeks. The voltage range was 2.75-4.2V. The battery's first week charging capacity, initial efficiency, the ratio of the second week charging capacity to the first week charging capacity (recorded as 1C / 0.1C), and the ratio of the 102nd week charging capacity to the 3rd week charging capacity (recorded as 100-week cycle retention rate) were recorded.

[0102] The test results are shown in Tables 1 and 2.

[0103] Table 1

[0104]

[0105]

[0106] Table 2

[0107] sample First week coulomb efficiency, % 1C / 0.1C, % 100-week cycle retention rate, % Example 1 87.95 96.7 97.73 Example 2 88.12 97.1 97.71 Example 3 88.07 96.9 98.87 Example 4 87.60 97.7 97.23 Example 5 88.12 98.3 95.82 Example 6 88.36 98.14 96.88 Example 7 87.80 98.02 96.74 Example 8 88.76 98.56 96.87 Example 9 88.03 97.86 96.53 Example 10 88.11 97.81 96.64 Embodiment 11 87.94 98.41 96.21 Example 12 88.15 98.33 96.53 Comparative Example 1 86.83 94.42 91.43 Comparative Example 2 86.52 95.84 90.88 Comparative Example 3 86.99 95.71 92.96 Comparative Example 4 44.32 100.27 85.43 Comparative Example 5 87.32 96.71 93.31 Comparative Example 6 87.65 96.52 93.43

[0108] From the above description, it can be seen that the above-mentioned embodiment of the present invention realizes the improvement of the rate performance of the pole piece itself by performing three magnetization treatments on the negative pole piece coated with graphite active material, and ultimately manifests as the improvement of various electrical properties of the lithium-ion battery, specifically: improving the fast charging performance of the battery cell, especially under high rate conditions, can significantly improve the constant current ratio of the battery cell; at the same time, there is also a certain degree of improvement in the cycle performance.

[0109] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a graphite negative electrode sheet, characterized in that: The following steps are involved: Step S1, mixing: adding graphite, a conductive agent and a binder into a solvent and mixing to obtain a slurry; Step S2, coating: preparing a current collector, and coating the slurry on at least one side surface of the current collector to obtain a coated electrode sheet, wherein the coated electrode sheet has a length direction and a width direction that are perpendicular to each other; Step S3, magnetization: periodically performing N groups of magnetization treatments on the coated electrode sheet to obtain the graphite negative electrode sheet, wherein N is an integer ≥ 1; Each group of magnetization treatments includes a first magnetization performed along a first direction, a second magnetization performed along a second direction, and a third magnetization performed along a third direction. The first magnetization, the second magnetization, and the third magnetization are performed in any order, and the first direction is perpendicular to the plane direction of the coated electrode sheet, and the second direction and the third direction are perpendicular to each other and parallel to the plane direction of the coated electrode sheet.

2. The method for preparing a graphite negative electrode sheet according to claim 1, characterized in that: In step S3, N=1, the first direction is perpendicular to the plane direction of the coated electrode sheet; The second direction is parallel to the plane direction of the coated electrode sheet and perpendicular to the length direction of the coated electrode sheet; The third direction is parallel to the plane direction of the coated electrode sheet and perpendicular to the width direction of the coated electrode sheet; Preferably, the magnetic field strengths used in the three magnetization treatments are each independently 0.5 to 1.5 T.

3. The method for preparing a graphite negative electrode sheet according to claim 2, characterized in that: The time of the first magnetization, the second magnetization and the third magnetization are each independently 1 to 120 seconds.

4. The method for preparing a graphite negative electrode sheet according to any one of claims 1 to 3, characterized in that: The particle size D50 of the graphite is 3 to 20 μm; Preferably, the graphite is natural graphite and / or artificial graphite, more preferably natural graphite.

5. The method for preparing a graphite negative electrode sheet according to any one of claims 1 to 4, characterized in that: The weight ratio of the sum of the weights of the conductive agent and the binder to the weight of the graphite is (10-2):(90-98), the solid content of the slurry is 30-60%, and the coating viscosity is 3000-7000 Pa·s.

6. The method for preparing a graphite negative electrode sheet according to any one of claims 1 to 5, characterized in that: The conductive agent is selected from one or more of acetylene black, carbon black, conductive graphite, carbon fiber, carbon nanotube and graphene; and / or the binder is selected from one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyaniline and citric acid; Preferably, the solvent is water.

7. The method for preparing a graphite negative electrode sheet according to any one of claims 1 to 6, characterized in that: Step S1 also includes: adding the first binder to the solvent, performing a first mixing, and obtaining an intermediate slurry; adding the graphite, the conductive agent, and the second binder to the intermediate slurry, performing a second mixing, and obtaining the slurry; Preferably, the first mixing time is 1 to 2 hours, and the second mixing time is 3 to 9 hours; Preferably, the first binder and the second binder are each independently one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, styrene butadiene rubber, polyacrylic acid, polyvinyl alcohol, polyaniline and citric acid; More preferably, the mixing is achieved using a twin-screw mixer and / or a double planetary mixer.

8. A graphite negative electrode sheet prepared by the method for preparing a graphite negative electrode sheet according to any one of claims 1 to 7.

9. The graphite negative electrode sheet according to claim 8, characterized in that: The OI value of the graphite negative electrode sheet is 0.1-1.

10. A lithium ion battery comprising a negative electrode sheet, a positive electrode sheet and an electrolyte, characterized in that: The negative electrode sheet is the graphite negative electrode sheet according to claim 8 or 9.

Citation Information

Patent Citations

  • Negative electrode material for quickly rechargeable graphite lithium-ion battery and preparation method of negative electrode material

    CN105024075A

  • Preparation method of high-rate fast-rapid graphite

    CN106981632A

  • Manufacturing method of cathode pole piece of lithium ion battery

    CN102709524A

  • Composite negative plate and preparation method thereof, lithium ion battery and power utilization device

    CN114335416A

  • Method for improving performance of total battery by regulating and controlling preferred orientation of lithium cobalt oxide crystal face through vertical magnetic field

    CN117080353A

Cited By

  • In-situ monitoring method for deintercalation of active ions in active material

    CN120992994A

  • Graphite negative electrode sheet and manufacturing method therefor, and lithium-ion battery

    WO2026066018A1